2022
DOI: 10.22271/27069567.2022.v4.i2a.399
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neutrophil to lymphocyte ratio in patients with diabetic nephropathy

Abstract: To assess neutrophil to lymphocyte ratio in patients with diabetic nephropathy. Materials and Methods: The present study was conducted with the aim of assessing Neutrophils to Lymphocytes ratio (NLR) in patients with Diabetic Nephropathy. A total of 50 type 2 diabetic patients were enrolled and were divided into two study groups as follows: Group A-Diabetic Patients diagnosed with Diabetic Nephropathy, and Group B-Diabetic patients without Diabetic Nephropathy. Baseline demographic and clinical details of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another study by Singh et al reported similar results, showing that the NLR could be considered a reliable predictive marker in diabetic nephropathy [ 21 ]. In a study by Khan et al, the NLR of subjects with type 2 diabetes and increased albuminuria was markedly elevated [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Singh et al reported similar results, showing that the NLR could be considered a reliable predictive marker in diabetic nephropathy [ 21 ]. In a study by Khan et al, the NLR of subjects with type 2 diabetes and increased albuminuria was markedly elevated [ 22 ].…”
Section: Discussionmentioning
confidence: 99%